Functional-semantic features of fashion and design terms in the parallel corpus (in the example of English and Uzbek texts) - Nastinova, Ezoza; Xaitqulov, Zahriddin (The Lingua Spectrum, 2025)
Using a parallel corpus, this paper compares and contrasts the functional-semantic characteristics of fashion and design terms in Uzbek and English. It investigates the usage, translation, and adaptation of terms from textile-related, interior design, and apparel vocabulary in both languages, exposing patterns of translation, cultural subtleties, and semantic alterations. The study emphasises how sociocultural elements and linguistic structure affect how fashion-related language is understood and equated. Translation difficulties, such as culturally restricted ideas and context-dependent meanings, are given particular consideration. The study shows how corpus-based techniques can be used to find patterns, collocations, and usage frequency in different languages. It also demonstrates how cultural adaptation affects the choice of terms and the efficacy of particular translation techniques.The results guide translation procedures in this specialised subject and aid in the creation of bilingual fashion and design dictionaries. All things considered, the study advances our knowledge of cross-linguistic and cross-cultural dynamics in the transmission of fashion and design.